Effect of oxygen tension and antioxidants on the developmental competence of buffalo oocytes cultured in vitro - El-Sanea, Amro M. (Vet World, 2021)
AIM: Oxidative stress (OS) is one of the major disruptors of oocyte developmental competence, which appears due to the imbalance between the production and neutralization of reactive oxygen species (ROS). MATERIALS AND METHODS: In Experiment 1, buffalo oocytes were in vitro matured, fertilized, and cultured at 38.5°C under 5% CO(2) + 20% O(2) in standard CO(2) incubator (OS) or under 5% O(2) + 5% CO(2) + 90% N(2) (Multi-gas incubator, low O(2)). In Experiment 2, buffalo cumulus oocytes complexes (COCs) were matured in Basic maturation medium (BMM) composed of TCM199+ 10% FCS+ 10 µg/ml FSH+ 50 µg/ml gentamicin (control group) or in BMM supplemented with 50 μM ascorbic acid (ascorbic acid group) or 3.0 mM glutathione (glutathione group) or 10(-5) M melatonin (melatonin group) and cultured at 38.5°C under 20% O(2) for 24 h. Matured buffalo oocytes in control, ascorbic acid, or melatonin groups were fertilized and zygotes were cultured for 8 days under the same conditions. RESULTS: In both experiments, maturation, cleavage, and blastocyst rates were recorded. Results showed that culture of buffalo oocytes under low O(2) (5% O(2)) significantly increased maturation, cleavage, and blastocyst rates (p<0.05). Meanwhile, under 20% O(2), addition of 10(-5) M melatonin or 50 μM ascorbic acid to in vitro maturation (IVM) medium significantly improved cumulus cell expansion, nuclear maturation rates of buffalo oocytes (p<0.05), and increased cleavage and blastocyst rates (p<0.05). CONCLUSION: About 5% O(2) is the optimum condition for in vitro production of buffalo embryos, and addition of 10(-5) M melatonin to IVM medium for oocytes cultured under 20% O(2) could alleviate the adverse effect of high oxygen tension and increased embryo yield.